Intelligent Robotics and Applications 8th International Conference, ICIRA 2015, Portsmouth, UK, August 24-27, 2015, Proceedings, Part I - Liu, Honghai; Kubota, Naoyuki; Zhu, Xiangyang; Dillmann, Rüdiger; Zhou, Dalin (Lecture Notes in Artificial Intelligence, 2015)
This three volume set LNAI 9244, 9245, and 9246 constitutes the refereed proceedings of the 8th International Conference on Intelligent Robotics and Applications, ICIRA 2015, held in Portsmouth, UK, in August 2015. The 60 papers included in the first volume are organized in topical sections on analysis and control for complex systems; marine vehicles and oceanic engineering; drives and actuators' modeling; biomechatronics in bionic dexterous hand; robot actuators and sensors; intelligent visual systems; estimation and identification; and adaptive control system.